High prevalence of Haplorchis taichui metacercariae in cyprinoid fish from Chiang Mai Province, Thailand - Kumchoo K. (2014)
This study aimed to investigate Haplorchis taichui metacercarial infection in fish collected from the Chom Thong and Mae Taeng districts, Chiang Mai Province during November 2001 to October 2002. A total 617 cyprinoid fish of 15 species were randomly collected and examined for H. taichui metacercariae. All the species of fish were found to be infected with H. taichui. The infection rates were 91.4% (266/290) and 83.8% (274/327), with mean intensities of 242.9 and 107.4 in the Chom Thong and Mae Taeng districts, respectively. The portion of the fish body with the highest metacercarial density was the muscles, and second, the head, in both districts. In addition, the fish had mixed-infection with other species of trematodes, namely: Centrocestus caninus, Haplorchoides sp, and Haplorchis pumilio.